Children's rights in New Zealand law and society - Austin, Graeme W (Victoria University of Wellington Law Review, 1995)
This article explores the various sources of children's rights in New Zealand law. These are found in legislation, common law and international documents. The results of a survey of schools and community agencies dealing with children are contained in the latter part of the article. Very little formal recognition of children's rights is found in school charters and mission statements. Children's rights and children's welfare are often equated. Funding for this project was provided by the New Zealand Law Foundation.